2019
DOI: 10.1007/s12517-019-4995-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size and adsorption pressure on methane gas desorption and diffusion in coal

Abstract: A self-developed gas desorption and diffusion experimental system was used to conduct isothermal methane gas desorption and diffusion experiments, and the pore structure of coal samples was analyzed. A new mathematical model for gas diffusion in coal particles was established, and the diffusion coefficient was calculated using the new model. The influences of particle size and the adsorption equilibrium pressure on the methane gas diffusion rate, gas diffusion quantity, and diffusion coefficient were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The methane diffusivity was measured from the slope of the early time desorption rate curve (Figure ) at various isotherm pressures based on the USBM volumetric desorption approach. The diffusion coefficient increases with an increase in the shale particle size (Figure ), which agrees with the observation for coal samples . Shale particle diameter affects the dynamic gas production process, in which a larger particle diameter leads to a longer path of diffusion …”
Section: Discussion On Resultssupporting
confidence: 87%
“…The methane diffusivity was measured from the slope of the early time desorption rate curve (Figure ) at various isotherm pressures based on the USBM volumetric desorption approach. The diffusion coefficient increases with an increase in the shale particle size (Figure ), which agrees with the observation for coal samples . Shale particle diameter affects the dynamic gas production process, in which a larger particle diameter leads to a longer path of diffusion …”
Section: Discussion On Resultssupporting
confidence: 87%
“…The methane adsorption rate increases with increasing bedding plane angle, and the more effective paths for methane flow within the specimen, the faster the initial flow rate. Li et al (2019b) concluded from methane desorption and diffusion experiments that larger coal particle size in coal will result in a slower gas diffusion rate and longer desorption time. Zhou et al (2019) analyzed the potential energy change characteristics of methane near the pore throat based on Leonard-Jones potential function (Eq.…”
Section: Effect Of Pore Structures On Sorptionmentioning
confidence: 99%
“…e influence of particle size on gas loss is reflected in the influence of particle size on desorption speed. e larger the particle size of the coal sample, the smaller the initial kinetic diffusion parameter, and the smaller the amount of gas desorption at the same time [17,18]. On the other hand, the gas desorption behaviors of coal sample correlate with the surface area and depend significantly on porosity [19].…”
Section: Introductionmentioning
confidence: 99%